Corporate social responsibility in view of the United Nations Global Compact principles and its role in achieving sustainable development Case study of "CHIALI GROUP" Foundation - Zeddoun, DJamel; Zeradna, Mohamed; Kazi, CHoukri (Finance and Business Economies Review, 2022)
The study aims to determine the extent to which business enterprises apply the United Nations Global Compact principles for Social Responsibility and assessing the level of commitment of these institutions to achieving the Sustainable Development goals. The study was applied to the "CHIALI GROUP" Foundation located in Sidi BelAbbes where a questionnaire composed of 50 items has been distributed, and analyzed using SPSS V.22 software. The study found that the foundation under study has adopted the principles of social responsibility stipulated in the United Nations Global Compact, and also the foundation seeks to contribute to achieving sustainable development goals. The study found as well a strong positive correlation between the adoption of corporate social responsibility and the sustainable development goals.